Highly stable 3D/2D WO3/G-C3N4 z-scheme heterojunction for stimulating photocatalytic co2 reduction by H2O/H2 to CO and CH4 under visible light - Tahir, B. (Elsevier Ltd., 2020)
Well-designed 3D/2D WO3/g-C3N4 microspheres with an effective interfacial contact, synthesized through facile single step hydrothermal method, for stimulating photocatalytic CO2 reduction under visible light has been investigated. The direct growth of WO3 microspheres with g-C3N4 enables good interaction among the both semiconductors, enabling proficient charge carrier separation. Highest CO and CH4 production over WO3/gC3N4 of 145 and 133 μmole g−1 h−1 was achieved, 1.91 and 4.03-fold higher than using pristine g-C3N4, respectively. This enhanced photoactivity was noticeable due to the synergistic effect with the larger interfacial contact area and proficient charge carrier separation. More importantly, CH4 and CO production was increased by 2.51 and 1.64-fold with optimized H2O/CO2 feed ratio due to efficient adsorption of both the reactants. Similarly, by replacing water with H2, CO2 reduction efficiency was increased by 1.5 and 2.6-fold higher for CO and CH4 production. The photon flux also has a significant contribution in CO2 reduction, whereas, 1.6 and 1.7-fold higher CO and CH4 production observed by increasing light intensity. The stability analysis reveals continuous production of CO and CH4 in cycles without any obvious deactivation under both the lower and higher light intensity. This work demonstrates a new approach to construct composite heterojunction and would be beneficial for further investigation in selective CO2 conversion to solar fuels.